Oxidative stability of plant hydroalcoholic extracts assessed by EPR spin trapping under forced ageing conditions: A myrtle case study. (15th January 2019) - Sanna, Daniele; Mulas, Maurizio; Molinu, Maria Giovanna; Fadda, Angela
Highlights: Myrtle extracts' oxidative stability is tested by EPR under forced aging conditions. Two berry/media ratio and media with 60–90% ethanol are tested over storage. Ω based on lag time, adduct concentration and formation rate measures the oxidative stability. Ω is strongly influenced by the extraction medium and by the time of storage. There is an inverse correlation between Ω and ellagic acid concentration. Abstract: The oxidative stability of myrtle hydroalcoholic extracts was measured, over storage time, with the EPR spin trapping method under forced ageing conditions. The extracts were prepared with 150 and 300 g l −1 of berries and extraction media with ethanol ranging from 60 to 90%. Two radicals were detected: the PBN–1-hydroxyethyl adduct and the tert -butyl aminoxyl radical. A dimensionless parameter (Ω) calculated on the basis of the lag time, the rate of formation and concentration of the radical species was used to estimate the extracts' oxidative stability. Ω was strongly influenced by the extraction medium, being lower in extracts with ethanol 60%, and by the time of storage. An inverse correlation was calculated between Ω and ellagic acid concentration, thus suggesting the role of this phenolic acid in the antioxidant properties of the extracts. The radical scavenging activity of the extracts against the hydroxyl radical was also measured.